The association of posttraumatic stress disorder and chronic medical conditions by ethnicity - Valentine, Sarah E. (J Lat Psychol, 2017)
Our study extends the literature on associations between posttraumatic stress disorder (PTSD) and chronic medical conditions by assessing differences in the magnitude of these relations by ethnicity. We examined group differences in the magnitude of the relation between PTSD and chronic medical conditions (cardiovascular disease [CVD], hypertension, obesity, diabetes). We obtained data from Latino (n = 3,224) and non-Latino white (n = 4,180) respondents from the Collaborative Psychiatric Epidemiology Surveys. Logistic regression models were constructed to test for the modification of the effect of PTSD on chronic medical conditions by ethnicity, and then by nativity. Unadjusted models revealed significant interactions between Latino ethnicity and PTSD for odds of diabetes (OR = 2.18 [Latino] v. 0.81 [non-Latino white]), CVD (OR = 3.23 [Latino] v. 1.28 [non-Latino white]), and hypertension (OR = 1.61 [Latino] v. 0.98 [non-Latino white]). Among U.S.-born Latinos, we found a significant interaction between ethnicity and PTSD for odds of CVD (OR = 4.18 [Latino] v. 1.28 [non-Latino white]) and diabetes (OR = 2.27 [Latino] v. 0.81 [non-Latino white]). These findings attenuated in adjusted models with the exception of differences in PTSD and odds of diabetes among Latinos (including aggregated group & U.S.-born) compared to non-Latino whites. Our findings support the need for further research on the complex relations between PTSD and chronic conditions, including the investigation of conditional risk by Latino sub-groups.